Network governance : Alliances, Cooperatives and Franchise Chains - Windsperger, Josef; Cliquet, Gerard; Hendrikse, George; Ehrmann, Thomas (Contributions to Management Science, 2013)
The current book on Nework Governance contributes to the literature by offering new perspectives on network goals and performance, inter-organizational learning and trust in alliances, corporate governance issues in cooperatives, governance of cross-border retail networks, contract design and governance innovations in cooperatives and fanchising.